A new genus, Rubroboletus, to accommodate Boletus sinicus and its allies - Zhao, Kuan; Wu, Gang; Yang, Zhuliang (Phytotaxa, 2014)
Rubroboletus is erected as a new genus to accommodate Boletus sinicus and its allies based on morphological and molecular evidence. Morphologically, Rubroboletus differs from the remaining genera in Boletaceae by the combination of a reddish pileal surface, an orange-red to blood red surface of the hymenophore, yellow tubes, pink to red reticula or spots on the yellow background of the stipe, a bluish color-change when injured, a non-amyloid context, smooth spores which are olive-brown in deposit, and an interwoven trichodermal pileipellis. Our phylogenetic analyses based on five gene markers (ITS, nrLSU, tef1-α, rpb1 and rpb2) recognized eight species in the genus, including one new species and seven new combinations. A key to the eight species is provided.